Perancangan Sekolah Alam Bahari Bandar Bakau Di Dumai - Adhienirma, Habib Surya; Firzal, Yohannes; Faisal, Gun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Green school is an informal school wich focus on character education for children about the preservation of the nature coast. For that the green school of bahari bandar bakau became a place in accordance with the curriculum of basic education to optimize green school of bandar bakau informal standards become formal. In the design this green school of bahari bandar bakau will be done with the contextual approach coastal architecture within the Dumai coastal areas, also uses the concept of archipelago built space values so that the green school can remember and demonstrated the importance values of the archipelago built space. Some indicators which become the state of the art is sustainablility, harmony of nature, the climate response, collective consciousness, intelligence and knowledge of the culture as a basic for generating design of green school in accordance with national curriculum standards and contextual with the maritime environment.Keywords: green school, maritime, coastal architecture, contextual